Acupuncture Relieves Motion Sickness via the Irβ-Erk1/2-Dependent Insulin Receptor Signalling Pathway. Issue 3 (June 2018) - Tian, Dawei; Mo, Fengfeng; Cai, Xingjian; Miao, Zhiyuan; Xiao, Feng; Chang, Yifang; Wu, Lusha; Tang, Yuxiao; Wang, Xin; Ye, Chen; Qian, Xiaolu; Gu, Wei; et al.
Objective: Acupuncture has been widely used for the treatment of motion sickness (MS), but the underlying mechanisms are unclear. The aim of this research was to study the mechanism of acupuncture in the treatment of MS. Methods: To observe the effects of acupuncture in the treatment of MS, 80 rats were randomised into five groups that were subjected to acceleration and either remained untreated (CTRL), or received restraint (REST), scopolamine (SCOP) or acupuncture at SP4 (sham) or PC6+ST36 (verum) acupuncture points. To study the mechanism underlying the effects of acupuncture in the treatment of MS, 48 rats were randomised into three groups: acupuncture+extracellular regulated protein kinases (ERK) 1/2 inhibitor (ERKinh), acupuncture+insulin receptor (IR) antagonist (IRant), and acupuncture+vehicle (VEH). After acceleration, the MS index (MSI) and spontaneous activity (SA) of the rats were recorded. Serum stress hormones, Fos-positive cells, c-fos mRNA in the vestibular nucleus, and IRβ-, p-IRβ-, ERK1/2- and p-ERK1/2-positive cells in the dorsal motor nucleus of the vagus nerve (DMV) were detected. Results: After acceleration, MS symptoms in the PC6+ST36 and SCOP groups were reduced compared with the CTRL, REST, and SP4 groups. The number of p-IRβ- and p-ERK1/2-positive cells and insulin levels were higher in the PC6+ST36 group than in the CTRL, REST, and SP4 groups. After ERK1/2 inhibitor and IR antagonist treatment, MS symptoms in the VEH group were lower than in the ERKinh and IRant groups. Conclusions: Our study demonstrates that acupuncture significantly alleviates MS through the IRβ-ERK1/2-dependent insulin receptor signalling pathway in the DMV